Assessing Youth Response to Media and Information Literacy Competencies through an Online Course: An Empirical Study and Comparative Analysis - Part 2 (Global Journal of Human-Social Science, 2021)
This article is Part 2 of the paper titles Assessing Youth Response to Media and Information Literacy Competencies through an online course: An Empirical Study and Comparative Analysis presented into articles. Part 1 offers a discourse on the urgency for MIL to empower youth, the context, and a suggested methodology. This second part shows the principal findings obtained with this research and some discussion. 1 Part 2 of the study is presented here. See Part 1 earlier in this Journal Volume. This study explores how best to disseminate media and information literacy (MIL) skills and inform goaloriented development of educational policies and strategies. Using the qualitative and quantitative method, the research, completed in 2018, investigated youth responses to online and offline personal, social, economic, political and cultural challenges and opportunities before and after acquiring MILrelated skills. It involved a sample of 1,735 14-to 30-year-olds who reflected on their knowledge of MIL and their attitudes toward social and democratic issues such as freedom of expression (FOE), freedom of information (FOI), intercultural dialogue (ICD) and interreligious dialogue (IRD).
Keywords: media and information literacy; mil education; intercultural dialogue; interreligious dialogue; educational strategies; mil skills